2018
DOI: 10.1016/j.patcog.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Product graph-based higher order contextual similarities for inexact subgraph matching

Abstract: Many algorithms formulate graph matching as an optimization of an objective function of pairwise quantification of nodes and edges of two graphs to be matched. Pairwise measurements usually consider local attributes but disregard contextual information involved in graph structures. We address this issue by proposing contextual similarities between pairs of nodes. This is done by considering the tensor product graph (TPG) of two graphs to be matched, where each node is an ordered pair of nodes of the operand gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Among the numerous graph matching methods proposed over the years, we found that the method proposed by Dutta et al [ 54 ] matches our constraints. Indeed, their approach is based on the computation of higher order similarities between pairwise nodes and edges of input graphs.…”
Section: Pattern Recognitionmentioning
confidence: 54%
See 3 more Smart Citations
“…Among the numerous graph matching methods proposed over the years, we found that the method proposed by Dutta et al [ 54 ] matches our constraints. Indeed, their approach is based on the computation of higher order similarities between pairwise nodes and edges of input graphs.…”
Section: Pattern Recognitionmentioning
confidence: 54%
“…In this way, the assignment is solved with linear approximation functions. A recent method [ 54 ] was proposed to compute contextual similarities between pairwise nodes and edges using a remastered random walk. This gives high-order features without dealing with hypergraphs, but still linearly solves the assignment.…”
Section: Pattern Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most current GM algorithms are second-order or high-order GM methods [ 22 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Second-order GM methods combine the similarity of vertices-to-vertices and edges-to-edges.…”
Section: Pairwise Point Set Registrationmentioning
confidence: 99%